2007
DOI: 10.1080/10916460500528854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Composition on the Physical Characteristics of Paving Asphalts

Abstract: The simplest general compositional model considers asphalt to be made up of asphaltenes, heavy oils, and resins. In the present study the extent of similarity between the properties and composition of various types of asphalt obtained from different sources has been carefully explored. It shows how ductility, penetration, and softening point are related to the chemical nature of paving asphalts in the range 41-58 softening points. Asphalt properties are found to be a direct function of its chemical constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 20 publications
3
18
0
15
Order By: Relevance
“…Petersen (1984) discussed in detail the chemical composition of asphalt as related to its durability. Detailed investigations were carried out in the past relating the chemical composition of asphalt to the rheological properties by a number of researchers, including Rostler and White (1959); Corbett (1965); Gaestel, Smadja, and Lamminan (1971); Moschopedis and Speight (1977); Poirier and Sawatzky (1992); Lesueur, Gerard, Letoffe, Planche, and Martin (1996); Liu et al (1997);Loeber, Muller, Morel, and Sutton (1998); Pauli and Branthaver (1998);Christopher, Richard, and Charles (1999); Robertson (2000); Leon, Rogel, and Espidel (2000); Redelius and Soenen (2005); and Oyekunle (2000Oyekunle ( , 2007. With significance evidence from the literature, one can conclude that each fraction or combination of fractions perform separate functions in respect to physical properties, and it is logical to assume that the overall physical properties of one asphalt are dependent on the combined effect of these fractions and the proportions in which they are present (Petersen, 1984).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Petersen (1984) discussed in detail the chemical composition of asphalt as related to its durability. Detailed investigations were carried out in the past relating the chemical composition of asphalt to the rheological properties by a number of researchers, including Rostler and White (1959); Corbett (1965); Gaestel, Smadja, and Lamminan (1971); Moschopedis and Speight (1977); Poirier and Sawatzky (1992); Lesueur, Gerard, Letoffe, Planche, and Martin (1996); Liu et al (1997);Loeber, Muller, Morel, and Sutton (1998); Pauli and Branthaver (1998);Christopher, Richard, and Charles (1999); Robertson (2000); Leon, Rogel, and Espidel (2000); Redelius and Soenen (2005); and Oyekunle (2000Oyekunle ( , 2007. With significance evidence from the literature, one can conclude that each fraction or combination of fractions perform separate functions in respect to physical properties, and it is logical to assume that the overall physical properties of one asphalt are dependent on the combined effect of these fractions and the proportions in which they are present (Petersen, 1984).…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Colloidal instability (Gaestel) index I c was calculated from SARA fractions, and with aging showed increased content level of asphaltenes [12,24,59]. The I c is usually used to compare the stability of different bitumens.…”
Section: Bitumen Fractional Groups (Sara) Composition Test Proceduresmentioning
confidence: 99%
“…According to the colloidal composition, there are three types of bitumen behaviours [10]: sol (viscous), sol-gel (viscoelastic), and gel (elastic). Bitumen colloidal stability was determined by using the instability index I c -also called the Gaestel index [11]-which increases with an increased level of asphaltenes [12]. Thus, the asphaltenes are the most important components of a colloidal system of bitumen, whose quantity and interaction with the resins, aromatics, and saturates defines the rheological properties of bitumen.…”
mentioning
confidence: 99%
“…So, it was prone to segregate during storage. To solve the storage problem, Oyekunle found that some kinds of acid will improve the storage of rubber asphalt [9]. Al-Mansob et al investigated the effects of Al 2 O 3 addition to the base asphalt and epoxidised natural rubber modified asphalt (ENRMA), including the physical properties, storage stability, rheological properties, and microstructure of the binders [10].…”
Section: Introductionmentioning
confidence: 99%